The Norton anthology of American literature (Norton, 2012)
Read by more than 2.5 million students over 30 years, The Norton Anthology of American Literature sets the standard and remains an unmatched value. The Eighth Edition features a diverse and balanced variety of works and thorough but judicious editorial apparatus throughout. The new edition also includes more complete works, much-requested new authors, 170 in-text images, new and re-thought contextual clusters, and other tools that help instructors teach the course they want to teach. The Norton Anthology of American Literature is now available as an interactive ebook, at just a fraction of the print price.